Deep mutational scanning reveals EGFR mutations conferring resistance to the 4th-generation EGFR tyrosine kinase inhibitor BLU-945 - Yueyang Wang; Yuan Hao; Michela Ranieri; Tigran M. Abramyan; Lev Tsidilkovski; Michelle Hollenberg; Alfonso Lopez; Xavier T. R. Moore; Fiona Sherman; Jiehui Deng; Hayk Saribekyan; Garegin Papoian; et al. (npj Precision Oncology)
Abstract Fourth-generation EGFR tyrosine kinase are in development to overcome common resistance mutations. We performed deep mutational scanning (DMS) of the EGFR kinase domain in the context of L858R by introducing a saturation library of ~17,000 variants into Ba/F3 cells. DMS library-expressing cells were exposed to osimertinib or BLU-945 to identify escape mutations. L718X mutations were enriched across all conditions. BLU-945 specific mutations included K714R, K716T, L718V, T725M, K728E, K754E/N, N771S/T, T783I, Q791L/K, G863S, S895N, K929I, and M971L. A secondary DMS screen combining osimertinib and BLU-945, exclusively enriched for L718X mutations. Clinically, L718X mutations emerged in two patients treated with BLU-945. One patient with baseline EGFR L858R and L718Q mutations experienced early progression. Another with baseline EGFR L858R, T790M, and C797S acquired an L718V mutation at progression. This study demonstrate how comprehensive resistance profiling of targeted therapies can predict clinically relevant mutations and guide rational combinations to delay or prevent resistance.